A systematic review of physical activity: benefits and needs for maintenance of quality of life among adults with intellectual disability - Jacob, Udeme Samuel; Pillay, Jace; Johnson, Ensa; Omoya, Oluwatomilayo (Tomi); Adedokun, Adewale Philip (Frontiers in Sports and Active Living, 2023)
Adults with intellectual disabilities need regular physical activity. This review critically examined the evidence regarding physical activity interventions for adults with intellectual disability. A thorough search of various bibliographic databases such as PubMed, PsycINFO, BioMed Central and Medline identified 735 academic papers. The rigour of the research was evaluated, and the strength of the evidence was determined. A total of sixteen studies met the inclusion criteria. Various forms of physical activity were studied as interventions. The results of a critical review indicate that physical activity has a moderate to strong positive effect on weight loss, sedentary behaviour, and quality of life in adults with intellectual disabilities. It is essential to translate research in this area into practice by specifically designing physical activity programs for adults with intellectual disability.